2016
DOI: 10.1177/1469787416654794
|View full text |Cite
|
Sign up to set email alerts
|

Peer review as a strategy for improving students’ writing process

Abstract: Peer review is an established strategy for improving the quality of students’ writing. This study moves beyond the focus on outcomes to assess the peer-review process. In particular, this study focuses on the timing of the peer review, a highly structured feedback form, and student writers’ revisions after engaging in peer review. This study draws from a peer-review assignment conducted over 3 years in upper-division, discipline-specific courses. The data reveal these strategies force students to begin writing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
100
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 59 publications
9
100
2
2
Order By: Relevance
“…[5][6][7] Peer review has been consistently shown to increase students' writing performance as well as their learning retention. 8,9 Peer review has been shown to be an especially effective learning for English-language learners, even when their peer partners are also non-native speakers of English. 10,11 Students' consistent performance increase is generally attributed to a cluster of interrelated practical and cognitive factors.…”
Section: Background and Rationalementioning
confidence: 99%
See 4 more Smart Citations
“…[5][6][7] Peer review has been consistently shown to increase students' writing performance as well as their learning retention. 8,9 Peer review has been shown to be an especially effective learning for English-language learners, even when their peer partners are also non-native speakers of English. 10,11 Students' consistent performance increase is generally attributed to a cluster of interrelated practical and cognitive factors.…”
Section: Background and Rationalementioning
confidence: 99%
“…1 Substantive revision is a key practice of experts that we must often scaffold in students, and peer review serves as an organizing circumstance for such revisions with minimal investment of class time for turnaround. 8,11,12 Curricular economy belies a deeper factor for the consistent gains that students make through peer review activities. In addition to increasing feedback and revision cycles, peer review activities increase reflection around writing in ways that iterations do not.…”
Section: Background and Rationalementioning
confidence: 99%
See 3 more Smart Citations